Analisis Yuridis Tentang Perlindungan Hukum Bagi Ahli Waris Yang Tidak Hadir (Afwezig) Menurut KUHPerdata - Amelia, Meli; Wahyudi, Andri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The division of inheritance in Islam is a must. The distribution of property left by thedeceased is a manifestation of Islamic recognition of the existence of individual property rights. Individual property rights will end when a person dies, and transfers to the heirs. The process of implementing the property until it becomes an inheritancewhich will be distributed to the heirs, no one can postpone it. Since the determination of heirs to the part that must be obtained by each heir is a provision that must be implemented. The division of inheritance according to Islamic law is declared toexist, if the inheritance conditions are met. The fulfillment of the conditions of inheritance can entitle a person or heir to receive an inheritance. Between the conditions of